AP2A1 activates Rab7 to promote axonal autophagosome transport and slow the progression of Alzheimer’s disease - Yangyang Wang; Siyu Li; Xiao Liang; Jianing Fan; Shijie Li; Fanlin Zhou; Xiaoju Li; Mengmeng Lai; Dianmao Feng; Yu Li (Alzheimer’s Research & Therapy)
Abstract Background Dysregulation retrograde axonal transport in neurons results in autophagosome accumulation, enhancing amyloid β (Aβ) production and accelerating Alzheimer’s disease (AD) progression. Ras-associated GTP-binding protein 7 (Rab7) is pivotal in autophagosome maturation and their fusion with lysosomes, as well as in bidirectional axonal transport through interactions with partner proteins. Recent studies suggest that adapter-associated protein complex 2 subunit α1 (AP2A1) modulates retrograde axonal autophagosomes transport, regulates autophagy, and influences AD progression. However, the interplay between AP2A1 and Rab7, along with the molecular mechanisms underlying their impact on neuronal autophagy in AD, remains poorly understood. Methods We employed N2a/APPswe cells, primary hippocampal neurons exposed to Aβ oligomers, and APP/PS1 transgenic mice as AD models. To assess the impact of AP2A1 on Rab7 activity and autophagy, we conducted Rab7 pulldown activation assay, transmission electron microscopy (TEM), western blot and immunofluorescence (IF) staining were performed. The interaction between AP2A1 and Rab7 was examined by co-immunoprecipitation (Co-IP), IF staining and molecular docking. Live-cell imaging was utilized to monitor autophagosome axonal transport in primary hippocampal neurons. Aβ levels were quantified through immunohistochemistry and ELISA. Behavioral alterations in mice were evaluated using the Morris water maze, open field test, object recognition test and Y-maze. Results We observed reduced levels of AP2A1 and Rab7-GTP, accompanied by autophagosome accumulation, in AD models. Overexpression of AP2A1 restored autophagic flux in these cells. AP2A1 was found to bind and activate Rab7, facilitating the recruitment of retrograde axonal transport proteins DIC1 and RILP. Additionally, AP2A1 overexpression enhanced retrograde axonal autophagosome transport, reinstated autophagic flux, provided neuroprotection, and improved behavioral deficits in AD model mice through Rab7 activation. Conclusions Our findings demonstrate that AP2A1 activates Rab7 to restore autophagic function and mitigate AD progression, providing novel therapeutic perspectives for autophagy-targeted interventions in AD.